2003
DOI: 10.2176/nmc.43.1
|View full text |Cite
|
Sign up to set email alerts
|

Histologically Classified Venous Angiomas of the Brain: A Controversy.

Abstract: The term``venous angioma'' (VA) usually refers to a developmental venous anomaly (DVA). However, a group of vascular malformations called VAs shows no venous abnormalities on angiography. The clinical and histological features of histologically classified VAs were studied in eight patients who presented with hemorrhage or seizures to reevaluate these venous anomalies. Angiography showed no venous abnormalities in six patients. Histological study included immunostaining for smooth muscle actin and glial fibrill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 55 publications
1
31
0
4
Order By: Relevance
“…Consistent with the vast majority of international studies [11,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30], a slight male predominance of childhood intracranial tumors (M/F = 1.04) was noted in our Egyptian referral center. In this context, Rickert and Paulus [5], in their meta-analysis of 10,582 childhood brain tumors accumulated from 16 international surveys, reported that the M/F ratio was 1.29.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with the vast majority of international studies [11,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30], a slight male predominance of childhood intracranial tumors (M/F = 1.04) was noted in our Egyptian referral center. In this context, Rickert and Paulus [5], in their meta-analysis of 10,582 childhood brain tumors accumulated from 16 international surveys, reported that the M/F ratio was 1.29.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with this result, MC tumors accounted for 3.7% in the Brain Tumor Registry of Japan [18] and 3% in the US Childhood Brain Tumor Consortium [30]. Tumors involving more than one compartment were not recognized in most previous studies due to a lack of detailed radiological descriptions in most reported surveys.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In comparison to normal veins, histologically, DVAs are characterized by a composition of thin-walled vessels spread in normal neural parenchyma draining into a large caliber vein with a thicker wall 6 without a smooth muscle layer nor elastic lamina. 38 On contrast-enhanced CT, the venous collector of the DVA is readily detectable as a linear or curvilinear focus of enhancement, typically coursing from the deep white matter to a cortical vein or a deep vein or to a dural sinus. On MRIs, DVAs typically have a transhemispheric flow void on both T1-and T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the medullary veins composing the tributaries of the DVA are also known to have thinner walls, such veins may be more prone to bleed with this local venous hypertension. 20 DVAs generally fill later in the venous phase on catheter angiography. Our find- …”
Section: Discussionmentioning
confidence: 99%